The effect of athletic throwing events on the body composition and bone density in the limbs of throwing athletes - Kutác, P.; Uchytil, J.; Rygelová, M. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Throwing and putting are technical athletic events where one upper limb is dominant. The different load on the preferred and non-preferred limb may influence the body composition of the upper limb segments. The objective of the study is to assess the difference between the throwing and non-throwing upper limb in athletes specializing in javelin throw and shot put based on the segmental body composition analysis and kinetic analysis. METHODS: The group included 16 throwers at the age of 17.5±2.4 years. As a control group, we used 16 jumper athletes (age of 17.7±2.6 years). The symmetry of the load on upper limbs during a push-up was provided by the kinetic motion analysis. The segmental analysis of the upper limb body composition parameters was implemented using the method of dual X-ray absorptiometry. RESULTS: As to the power parameters, symmetry between the throwing and non-throwing upper limbs during the performance of a push-up was observed. The analysis of the upper limb body mass distribution showed statistically and objective significance in the bone mass values. The ratio of bone mass was higher in the throwing upper limb by 0.02 kg (P<0.0001) and bone density was higher by 0.07 g/cm2 (P<0.0001), the practical significance of the differences was major change for BMC (d=0.8) and medium for BMD (d=0.5). CONCLUSIONS: The results imply that the throw is a significant factor that contributes to the formation of bone mass.